Ecological Piety Based on the Qur'an: A Study of the Implementation of Environmental Verses at the Pesantren of Ath-Thaariq, West Java - Ahkmad Fatoni; Bambang Irawan; Muhamad Tamamul Iman (Ushuluna: Jurnal Ilmu Ushuluddin, 2025)
This article investigates Qur’an-based ecological piety through a qualitative case study of the Ath-Thaariq Ecological Islamic Boarding School in Garut, West Java. The study examines how Qur’anic teachings on food, agriculture, and ethical resource use are transformed into agroecological practices and everyday lifestyles that sustain land, water, and community relations. Data were collected through field observations, semi-structured interviews with eight informants (caretakers, teachers, students, and interfaith participants), and analysis of curriculum and program documents. The findings demonstrate that ecological piety is cultivated by internalizing the principles of amanah, mizan, anti-israf, and anti-fasad as daily ethical orientations; by applying a Qur’an-practice pedagogy that connects textual interpretation with farming activities; and by promoting interfaith collaboration through shared agricultural work. This study contributes to living Qur’an scholarship by reframing piety as ecological responsibility and offers a practical educational model for value-based environmental learning and religious moderation.